Optimal treatment strategies for small cell carcinoma of the uterine cervix: A retrospective multi-center study (KROG 19-03). (March 2021) - Cho, Won Kyung; Park, Won; Kim, Young Seok; Kang, Hyun-Cheol; Kim, Jin Hee; Kim, Kyung Su; Choi, Kyu Hye; Chang, Sei Kyung; Ahn, Ki Jung; Lee, Seok Ho; Kim, Sunghyun; Kim, Juree; et al.
Abstract: Objective: This multi-institutional study aimed to identify the optimal treatment strategy for small cell carcinoma of the cervix. Study design: We retrospectively collected the medical records of 166 patients diagnosed with small cell carcinoma of the uterine cervix from January 2000 to December 2015 from 13 institutions of the Korean Radiation Oncology Group. After excluding 18 (10.8 %) patients who initially had distant metastasis, the treatment outcomes of 148 patients were analyzed. Results: After a median 46.4 (1.4–231.9) months of follow-up, the 5-year progression-free survival (PFS) and overall survival (OS) rates of all patients were 45.9 % and 63.5 %, respectively. Distant metastasis was the dominant pattern of failure occurring in 67 patients (45.3 %). We stratified the patients according to the primary local treatment: primary surgery ( n = 119), primary radiotherapy (RT) ( n = 26), and no local treatment group ( n = 3). Although the primary RT group had advanced disease (FIGO stage ≧ IIB) more frequently than the primary surgery group (80.8 % vs. 47.9 %), the PFS and OS did not differ between the groups in multivariate analysis. Conclusion: Definitive RT is a reasonable local treatment option for small cell cervical cancer, particularly for advanced cases. Given the high rates of distant relapse, an effective systemic therapy protocol is warranted for small cell cervical cancer patients.